1985
DOI: 10.1128/iai.49.2.396-401.1985
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced oxidative burst in immunologically activated but not elicited polymorphonuclear leukocytes correlates with fungicidal activity

Abstract: Polymorphonuclear neutrophils (PMN) induced locally in immune mice by intraperitoneal injection of antigen exhibit enhanced fungicidal activity compared with PMN elicited with thioglycolate. The mechanism of the differences in these PMN populations was studied. Sublethal infection was used to produce immunity to Blastomyces dermatitidis. A correlation was sought between the ability of PMN to kill, or not kill, B. dermatitidis and the production of the oxidative burst, as measured by luminol-enhanced chemilumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 23 publications
2
6
0
Order By: Relevance
“…2 ). These results are consistent with those of previous studies that have demonstrated that VVC results in robust infiltration of PMNs, their associated oxidative burst ( 40 ), and the secretion of Th17 cytokines, including IL-22, IL17A, IL-17F, and IL-6, into the lavage fluid ( 17 , 34 , 41 44 ).…”
Section: Resultssupporting
confidence: 93%
“…2 ). These results are consistent with those of previous studies that have demonstrated that VVC results in robust infiltration of PMNs, their associated oxidative burst ( 40 ), and the secretion of Th17 cytokines, including IL-22, IL17A, IL-17F, and IL-6, into the lavage fluid ( 17 , 34 , 41 44 ).…”
Section: Resultssupporting
confidence: 93%
“…This conclusion was indicated by the meager luminol-enhanced CL responses and the inability of catalase, azide, or DMSO to inhibit killing. Although the H202-MPO-halide system is effective in killing B. dermatitidis (6,17), resident peritoneal macrophages are noted for their paucity of MPO (14), and this fact probably accounts for our findings. We speculate that activated macrophages could kill B. dermatitidis by an enhanced ability to discharge (degranulate) lysosomal contents (e.g., cationic proteins [16]) into the B. dermatitidis-macrophage interface.…”
mentioning
confidence: 59%
“…24,25 Although granulocytes have been shown in vitro to phagocytize B. dermatitidis, intracellular killing of organisms is poor but may be enhanced by lymphokines derived from immunologically stimulated T-lymphocytes. 26,27 These in vitro findings provide a link between cell-165 mediated immunity and polymorphonuclear leukocyte function, which were both implicated by the pathologic response noted.…”
Section: Pathogenesis or Host Defensesmentioning
confidence: 92%